2019
DOI: 10.1186/s12870-019-2096-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic analysis combined with tandem mass tags (TMT) labeling reveal the heterogeneity of strawberry stolon buds

Abstract: BackgroundRamet propagation in strawberry (Fragaria × ananassa) is the most effective way in production. However, the lack of systematically phenotypic observations and high-throughput methods limits our ability to analyze the key factors regulating the heterogeneity in strawberry stolon buds.ResultsFrom observation, we found that the axillary bud located in the first node quickly stepped into dormancy (DSB), after several bract and leaf buds were differentiated. The stolon apical meristem (SAM) degenerated as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…An early proteomics study (Fang et al 2011) described the major proteomic differences between the proximal internode (I-1) and the distal internode (I-2); however, the technique used would not have identified regulatory factors directing the different developmental outcomes. A more recent proteomics analysis of runner nodes identified 7271 proteins and revealed distinct protein differences among the tissues examined: the dormant axillary bud at node 1; the runner apical meristem; the runner producing axillary bud at node 2; and the developing leaves at node 2 (Guan et al 2019). However, no mechanism(s) for the developmental differences at node 1 and node 2 were obvious from the data that would account for the phenotype of the sin runners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early proteomics study (Fang et al 2011) described the major proteomic differences between the proximal internode (I-1) and the distal internode (I-2); however, the technique used would not have identified regulatory factors directing the different developmental outcomes. A more recent proteomics analysis of runner nodes identified 7271 proteins and revealed distinct protein differences among the tissues examined: the dormant axillary bud at node 1; the runner apical meristem; the runner producing axillary bud at node 2; and the developing leaves at node 2 (Guan et al 2019). However, no mechanism(s) for the developmental differences at node 1 and node 2 were obvious from the data that would account for the phenotype of the sin runners.…”
Section: Discussionmentioning
confidence: 99%
“…Strawberry runner growth from the meristem requires both cell division and cell elongation, which first result in a usually nonproductive node, although the node occasionally produces a thin, weak runner (Darrow 1929(Darrow , 1966Guan et al 2019). Following further extension, a clonal daughter plant capable of forming its own runners is produced at the tip.…”
mentioning
confidence: 99%
“…However, in China, during mid-October every year, favorable external environmental conditions lead to a significant sprouting of stolons. This excessive growth can disrupt the balance between the reproductive and nutritional growth processes of strawberries, resulting in yield reduction and loss of fruit quality [2]. Therefore, it is critical to effectively control the formation of stolons during the cultivation process of strawberries.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research ( 14 ), the consumption of hydrogen-enriched drinking water was shown to reduce endometrial tumor volume, density and weight in a xenograft mice model ( Figure S1 ), suggesting that drinking hydrogen-rich water (HRW) might be served as an effective treatment or adjuvant therapy for EC, while the mechanism of how they function remain unknow. To characterize the effect of hydrogen water on signal transduction, substrate specificity, and peptidase functional efficiencies, a new approach called quantitative multiplex substrate profiling by mass spectrometry (qMSP-MS) ( 15 ) which utilizes isobaric tandem mass tags (TMTs) was utilized herein. TMTs are available with different reactive groups, which enables deep proteome coverage for multiple samples in a reasonable amount of time ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%